Envisioning Criminology: Researchers on Research as a Process of Discovery - Maltz, Michael D (Springer, 2015)
This book covers research design and methodology from a unique and engaging point of view, based on accounts from influential researchers across the field of Criminology and Criminal Justice. Most books and articles about research in criminology and criminal justice focus on how the research was carried out: the data that were used, the methods that were applied, the results that were achieved. While these are all important, they do not present a complete picture. Envisioning Criminology: Researchers on Research as a Process of Discovery aims to fill that gap by providing nuance--the “back story” of why researchers selected particular problems, how they approached those problems, and how their background, training, and experience affected the approaches they took.